Body and Identity. Actions and Representations: Artistic creation as a vehicle for analysis and learning - Sánchez-Aranegui, Mónica Desirée (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
If we consider how the image and stereotypes influence the construction of the identity of primary and secondary students, it is essential to work on it in the classroom. Delimited in the actions and representations that are made about one’s own body and that of others in art, social networks, and advertising, we break down the information to rethink it and generate open discourses, debates and develop a critical thinking of the students about these questions. The project is carried out from art, adopting a transversal and multidisciplinary point of view, in the initial training of teachers.